Feasibility study on in-situ heat injection of Tongchuan oil shale and tar-rich coal based on TG-DTG - Yan, Heping; Wu, Xiurong; Li, Qiang; Fang, Yinghui; Bu, Qingfeng (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
In-situ thermal injection is an effective development method for low-value unconventional resources. The nonisothermal pyrolysis characteristics of Tongchuan oil shale and tar-rich coal were investigated by TG-DTG extrapolation. In addition, the pyrolyzed shale oil was analyzed. The results show that the pyrolysis of oil shale and tar-rich coal can be divided into three stages. The pyrolysis temperature intervals of both can be consistent. Compared with the oil shale, the ignition temperature of the mix decreased by 2.3%, and the burnout temperature increased by 1.4%. The pyrolysis index increased by 40.3%, the pyrolysis stability increased by 66.7%, and the content of oxygenated compounds increased by 552.4%. The conversion of oxygenated compounds to phenolic compounds was inhibited at the 20°C/min heating rate. In the air, the excessively fast heating rate caused the tar to condense earlier and coke on the sample surface. The pyrolysis index of the mix decreased from 3.2 to 1.8 times, while the pyrolysis stability increased by 6.7 times, respectively. The introduction of excessive oxygenated groups by the air increased the content of oxygenated compounds in the mix by 485.44% while the aromatic hydrocarbons decreased by 17.97%. It can be seen that the co-pyrolysis of oil shale and tar-rich coal can improve the ignition characteristics of oil shale. The co-pyrolysis of oil shale and tar-rich coal not only conforms to the distribution characteristics of both but also greatly cooperates with the topical chemical reaction method.